Boris Schnaiderman e Aleksander Púchkin: dois iniciadores - Vássina, Elena (Literatura e Sociedade, 2018)
The purpose of this essay is to explore "a Pushkin’s path" in the corpus of translation and essays by Professor Boris Schnaiderman and to point out the particular and unmistakable features of his method of working as a translator, researcher, critic and teacher. The focus of analysis is chosen not only to consider his view of Aleksandr Pushkin (1799-1837) as "initiator of modern Russian literature" but also to highlight the importance of both comparative analysis and the formal investigation of poetics used by Schnaiderman in the studies of Pushkin's creation.